Detection of chimeric alpha-defensin transcripts and peptides in mouse Paneth cells - Timmermans, Steven; Wallaeys, Charlotte; De Beul, Somara; Garcia-Gonzales, Natalia; Libert, Claude (Frontiers in Immunology, 2025)
IntroductionIn mammals, Paneth cells, located in the crypts of the small intestine, produceantimicrobial peptides that serve to keep the intestinal microbiome under control. a-Defensins are the primary antimicrobial peptides produced by these cells.MethodsWe used 148 publicly available bulk RNA-seq samples on purified PCs, proteomics on enriched purified PC proteins and Defa peptide activity assays to detect all Defa transcrips, including potential chimeric transcrips.ResultsWe identified 28 expressed Defa genes in mice, with up to 85% of Paneth cell RNA reads mapping to these genes. Chimeric mRNAs, involving sequences from two different Defa genes, were detected in most experiments. Despite their low abundance (less than 0.3%), mass spectrometry confirmed the presence of chimeric peptides. Synthetic versions of these peptides demonstrated antibacterial activity against multiple bacterial species.ConclusionWe show the existence of chimeric Defa transcripts and peptides in mice that are biologically active. We propose a possible stochatic mechanism or that the activation of the UPR patway may play a role in their production